METHANESULFONATE AND NON-SEA-SALT SULFATE IN DRIFTING-SNOW FROM EAST QUEEN MAUD LAND, EAST ANTARCTICA - オサダ, カズオ; OSADA, Kazuo (National Institute of Polar Research, 1996)
P(論文) Drifting-snow samples were collected at Mizuho Station from February to September 1986 and along traverse routes in east Queen Maud Land, East Antarctica, from October 1986 to January 1987. The typical sampling interval was about once a week. Variability in the methanesulfonate (MSA) and non-sea-salt (nss) SO_4^<2-> concentration levels suggests a seasonal relationship : high in summer and low in winter. The ratios of nssSO_4^<2->/MSA concentrations show a weak inverse seasonal relationship. The concentration levels of nssSO_4^<2-> correlate well with MSA concentration levels in the Mizuho Station samples obtained from late summer to early spring, suggesting that the dominant source of the nssSO_4^<2-> and MSA deposited in this region is marine biogenic dimethylsulfide. On the other hand the nssSO_4^<2->/MSA ratios from the traverse samples are significantly higher and deviate widely from the Mizuho Station regression line, implying a non-biogenic natural source for the nssSO_4^<2-> at the higher elevation inland locations. departmental bulletin paper